Early oral feeding following intestinal anastomoses in children is safe - Tunde T Sholadoye; Abdulrafiu F Suleiman; Philip M Mshelbwala; Emmanuel A Ameh (Wolters Kluwer Medknow Publications, 2012)
Background: Oral feeding following intestinal anastomoses is frequently delayed. In settings with limited utilisation of parenteral nutrition, this policy is problematic. This report evaluates the safety of early oral feeding following intestinal anastomoses in children. Materials and Methods: A prospective study including 64 children aged ≤12-year-old who had intestinal anastomoses for varying surgical indications over a 6-year period. Oral feeding was started within 72 hours following surgery, if there was no contraindication. Results: There were 41 (64.1%) boys and 23 (35.9%) girls aged 6 hours to 12 years (median, 6 years). The indication for surgery was perforated typhoid enteritis (33, 51.6%), intestinal atresia (8, 12.5%), colostomy closure for anorectal anomaly (8, 12.5%), intussusception (3, 4.7%) and ileostomy closure (3, 4.7%). Type anastomoses were 39 (60.9%) ileoileal, 4 (6.3%) colocolic, 8 (12.5%) jejunoileal and 4 (6.3%) ileocolic. Oral feeding was commenced in 17 (26.6%) of the patients within 48 hours, 36 (56.3%) by third day and 45 (70.3%) before fifth day post-operative. Feed-related complication occurred in 5 (7.8%) patients, 3 (8.3%) of which was in patients fed within 72 hours post-operative and 2 (7.1%) in those fed after 72 hours. Full oral feed was achieved by fifth and seventh day post-operative in 42 (65.6%) and 61(95.3%), respectively. Two (6.1%) patients had oral feeding stopped and recommenced at seventh day post-operative due to feed-related complications. Conclusion: Early oral feeding following intestinal anastomoses in children is safe, particularly in the setting of limited availability of parenteral nutrition.